Differential pH sensitivity of Kir4.1 and Kir4.2 potassium channels and their modulation by heteropolymerisation with Kir5.1. - Pessia, M; Imbrici, P; D'Adamo, M; Salvatore, L; Tucker, S (2001)
1. The inwardly rectifying potassium channel Kir5.1 appears to form functional channels only by coexpression with either Kir4.1 or Kir4.2. Kir4.1-Kir5.1 heteromeric channels have been shown to exist in vivo in renal tubular epithelia. However, Kir5.1 is expressed in many other tissues where Kir4.1 is not found. Using Kir5.1-specific antibodies we have localised Kir5.1 expression in the pancreas, a tissue where Kir4.2 is also highly expressed. 2. Heteromeric Kir5.1-Kir4.1 channels are significantly more sensitive to intracellular acidification than Kir4.1 currents. We demonstrate that this increased sensitivity is primarily due to modulation of the intrinsic Kir4.1 pH sensitivity by Kir5.1. 3. Kir4.2 was found to be significantly more pH sensitive (pK(a) = 7.1) than Kir4.1 (pK(a) = 5.99) due to an additional pH-sensing mechanism involving the C-terminus. As a result, coexpression with Kir5.1 does not cause a major shift in the pH sensitivity of the heteromeric Kir4.2-Kir5.1 channel. 4. Cell-attached single channel analysis of Kir4.2 revealed a channel with a high open probability (P(o) > 0.9) and single channel conductance of approximately 25 pS, whilst coexpression with Kir5.1 produced novel bursting channels (P(o) < 0.3) and a principal conductance of approximately 54 pS with several subconductance states. 5. These results indicate that Kir5.1 may form heteromeric channels with Kir4.2 in tissues where Kir4.1 is not expressed (e.g. pancreas) and that these novel channels are likely to be regulated by changes in intracellular pH. In addition, the extreme pH sensitivity of Kir4.2 has implications for the role of this subunit as a homotetrameric channel.